Konversi Bioetanol Hasil Fermentasi dari Ubi Jalar Putih (Ipomoea batatas LAM.) Menjadi Asam Asetat menggunakan Acetobakter aceti - Novi Kasari; Iryani Iryani; Bahrizal Bahrizal (Departemen Kimia FMIPA UNP, 2012)
Manufacture of acetic acid fermentation occurs in two stages, namely alcoholic fermentation and acetic acid fermentation. In alcoholic fermentation, materials containing starch or glucose converted into bioethanol by Saccharomyces cereviciae. After that in the second stage of bioethanol produced is oxidized to acetic acid by Acetobakter aceti. Has done research on the conversion of bio-ethanol from the fermentation of white sweet potato (Ipomoea batatas LAM.) to acetic acid using Acetobacter aceti. This study aimed to determine the amount of inoculum Acetobacter aceti and fermentation to produce acetic acid with the highest concentration. The research was conducted using completely randomized design (CRD) with two factors: the first factor is the amount of inoculum consists of three variations, namely 5, 10 and 15% (v/v), and the second factor is the length of fermentation which consists of 4 variations ie 3, 6, 9, 12 days. In this study, the concentration of ethanol obtained at 7.05422% with simultaneous fermentation by Aspergillus niger and Saccharomyces cereviciae with 2:1 ratio and fermentation time 56 hours. While the highest concentration of acetic acid is obtained in the addition of 10% inoculum and fermentation time of 12 days is equal to 0.553%.